Integrating student-made screencasts into computer-aided design education. (10th November 2017) - Zhang, Dongdong; Peng, Xiaobo; Yalvac, Bugrahan; Eseryel, Deniz; Nadeem, Uzair; Islam, Atiq
ABSTRACT: This paper presents the design strategies of an engineering education research project funded by the National Science Foundation (NSF) and discusses its findings. Study participants were the students who enrolled in "Mechanical Engineering Drawing" course and learned about computer-aided design (CAD). We grouped students into the control group and experimental group. Students in the control group received a traditional and teacher-centered instruction. The screencast tutorials were provided to them by their instructors. Students in the experimental group experienced a student-centered instruction. Instead of being provided instructor-prepared screencast tutorials, in the experimental group, students developed their own. They shared their tutorials with one another through an Internet portal; they reviewed and commented on each other's tutorials. These activities were student-centered. We captured students' attitudes towards engineering and their life-long learning skills before and after the semester, and their CAD knowledge at the end of the semester. The data used in this paper were collected in Fall 2014 and Spring 2015 and the findings are discussed in this paper. GRAPHICAL ABSTRACT: